Answer:
0
Step-by-step explanation:
[tex]\frac{2}{6(x-\frac{9}{10}) } =-2\frac{3}{4}[/tex]
1. The first step is to distribute the 6 to the [tex](x-\frac{9}{10})[/tex]:
[tex]\frac{2}{6x-7\frac{2}{10}} =-2\frac{3}{4}[/tex]
2. The second step is to get 6x-7 2/10 out of the denominator, so you have to multiply that on both sides which looks like this:
[tex]2 =-2\frac{3}{4}(6x-7\frac{2}{10})[/tex]
3. The third step is to distribute the -2 3/4 to the (6x-7 2/10):
[tex]\frac{-5}{4} * \frac{6x}{1}=\frac{-30x}{4}[/tex]
[tex]\frac{-5}{4} * \frac{72}{10}=\frac{-360}{40}[/tex]
[tex]\frac{-30x}{4}-\frac{-360}{40}=1\frac{x}{2}[/tex]
[tex]1\frac{x}{2} =2[/tex]
4. The fourth step is to get x by itself so you are going to change the mixed number into an improper fraction:
[tex]2+x=2[/tex]
5. All you do is subtract 2 from both sides of the equation and x=0